Development of an electron time of flight spectrometer for ultrafast pulse characterization and ultrafast dynamics studies - Timilsina, Pratap (Kansas State University, 2016)
This report presents the details of an electron time-of-flight (ETOF) spectrometer to be used for characterizing ultrafast electric field pulses. The pulses will range in pulse-duration from femtosecond to attoseconds and in wavelength from the far infrared (FIR) to the extreme ultra violet (XUV). By measuring the photoelectrons in the presence of two electric fields and their quantum interference we will be able to extract the amplitude and phase of the electric field. For XUV pulses this is the well-known streaking and Reconstruction of Attosecond Beating by Interference of Two-Photon Transition (RABITT) method. The ETOF is based on a set of tunable electrostatic lenses capable of detecting 0-150 eV electrons. In addition, we can selectively increase the photoelectron yield of the spectrum. The precise tuning of the electrostatic lens system is done with a Genetic Algorithm (GA) with an intensity fluctuation discriminator in the fitness.
Keywords: Electron time of flight; Ultrafast; Spectrometer